2019
DOI: 10.1007/s00127-019-01823-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical working conditions and subsequent disability retirement due to any cause, mental disorders and musculoskeletal diseases: does the risk vary by common mental disorders?

Abstract: Purpose Physical work exposures and common mental disorders (CMD) have been linked to increased risk of work disability, but their joint associations with disability retirement due to any cause, mental disorders or musculoskeletal diseases have not been examined. Methods The data for exposures and covariates were from the Finnish Helsinki Health Study occupational cohort surveys in 2000-2002, 2007 and 2012. We used 12,458 observations from 6159 employees, who were 40-60 years old at baseline. CMD were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Conversely, occupations without physical strain are often non-manual occupations which allow more flexibility for the workers in terms of how and when tasks are to be performed (Johansson and Lundberg 2009). A hindering effect in physically strenuous jobs could give rise to the more general association with poor self-rated health (Burr et al 2017), long-term sick leave (Andersen et al 2016;Sommer et al 2016;Sundstrup et al 2018), all-cause disability pension (Emberland et al 2017;Friis et al 2008;Halonen et al 2019;Jarvholm et al 2014;Karpansalo et al 2002;Labriola et al 2009;Lahelma et al 2012;Sommer et al 2016) and, consequently, loss of work-life expectancy (Schram et al 2020) demonstrated in previous studies. However, low education and a history of unemployment also seem to contribute to the explanation.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, occupations without physical strain are often non-manual occupations which allow more flexibility for the workers in terms of how and when tasks are to be performed (Johansson and Lundberg 2009). A hindering effect in physically strenuous jobs could give rise to the more general association with poor self-rated health (Burr et al 2017), long-term sick leave (Andersen et al 2016;Sommer et al 2016;Sundstrup et al 2018), all-cause disability pension (Emberland et al 2017;Friis et al 2008;Halonen et al 2019;Jarvholm et al 2014;Karpansalo et al 2002;Labriola et al 2009;Lahelma et al 2012;Sommer et al 2016) and, consequently, loss of work-life expectancy (Schram et al 2020) demonstrated in previous studies. However, low education and a history of unemployment also seem to contribute to the explanation.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…Heavy physical workload, including heavy manual handling, awkward body postures, repetitive and circulatory demanding work, seems to decrease the possibility of continuing to work up until an older age. Several studies have shown that disability pension is much more frequent among workers with heavy physical workload than in those without (Emberland et al 2017;Ervasti et al 2019;Friis et al 2008;Halonen et al 2019;Jarvholm et al 2014;Karkkainen et al 2013;Karpansalo et al 2002;Kjellberg et al 2016;Labriola et al 2009;Lahelma et al 2012;Prakash et al 2017;Ropponen et al 2014;Sommer et al 2016). Other studies have shown that long-term sickness absence, which usually precedes disability pension, is also more common (Andersen et al 2016;Sommer et al 2016;Sundstrup et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The covariates characterizing working conditions included adverse physical factors, job demands/control and shiftwork, as these job characteristics have been linked to disability. 18 , 21 , 22 Physical work exposures were based on an 18-item inventory. Following prior studies, 18 we used a factor analysis that divided the items into three factors: hazardous, physical workload and ‘office work’ exposures.…”
Section: Methodsmentioning
confidence: 99%
“… 18 , 21 , 22 Physical work exposures were based on an 18-item inventory. Following prior studies, 18 we used a factor analysis that divided the items into three factors: hazardous, physical workload and ‘office work’ exposures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation